Diagnostics and Description of a New Subspecies of Calluna vulgaris (L.) Hull from Western Siberia - Olga Cherepanova; Irina Petrova; Stanislav Sannikov; Yulia Mishchihina (Horticulturae, 2023)
The article presents the results of the study of fifty populations of common heather (Calluna vulgaris (L.) Hull) collected throughout its range. A phased comparative analysis (genetic, biochemical, anatomical, morphological, and ecological) was carried out with the estimation of indicators that included two key populations—Zavodouspenskoe (Pritobolye, Western Siberia) and Luga (Baltic, Eastern Europe). It was concluded that heather growing in Western Siberia should be identified as a separate taxonomic group, giving it the status of a subspecies. The gene pool of Pritobolye populations (including Zavodouspenskoe) is represented by the completely dominant (100%) monohaplotype S, which is not found anywhere else. The heather plant growing in Zavodouspenskoe has a longer lifespan. It is distinguished by larger linear leaf dimensions (length 2.06 ± 0.09 mm), thicker cuticle (4.77 ± 0.33 μm), increased number of trichomes (18.98 ± 0.56), and a reduced number of stomata (13.60 ± 0.63) than that growing in Luga. The new subspecies differs in biochemical composition: twice less content of epicatechin (average 1.992 ± 0.005 mg g−1), three times more myricetin (average 2.975 ± 0.005 mg g−1), twice as much chlorogenic acid (average 2.763 ± 0.004 mg g−1). An ecological feature is that C. vulgaris does not grow in the swamps of Western Siberia and has a small population. This species has a high horticultural potential and requires protection as its population in Western Siberia continues to decline rapidly.